Investigating the factors on e-commerce adoption among SMEs: a view of Technology Acceptance Model / Mohd Adha Shah Mohd Basir ... [et al.] - Mohd Basir, Mohd Adha Shah; Rashid, Umi Kartini; Nasuredin, Juzaimi; Ma'arof, Rabiatul Adawiyah (Faculty of Business and Management, 2023)
The adoption of e-commerce has become crucial for organizations, particularly among small and medium-sized enterprises (SMEs), to gain a competitive edge in the market since the emergence of the World Wide Web. Although previous research has investigated e-commerce adoption in different countries, there still needs to be studies, particularly in the Malaysian e-commerce industry, which has experienced accelerated growth due to the consumers' increased online shopping in response to the nationwide lockdown and movement restrictions. To address this gap, this study utilized the Technology Acceptance Model (TAM) to examine the relationships between organizational awareness (OA), perceived usefulness (PU), perceived ease of use (PEOU), and e-commerce adoption (EA) among SMEs in Johor. The study employed a quantitative approach and distributed an online questionnaire to the targeted respondents, resulting in 384 data sets that were analyzed using Statistical Packages for Social Sciences (SPSS) software, including descriptive and correlation analysis. The findings indicated that organizational awareness (OA), perceived usefulness (PU), and perceived ease of use (PEOU) had significant effects on ecommerce adoption (EA) among Johor SMEs. The results could assist the Johor State Government in developing and enhancing policies for the Digital Economy agenda and contribute to a better understanding of the factors that affect e-commerce adoption among SMEs in Johor. Finally, the study suggested future research directions based on the limitations and implications of the research.